Changes in apoptotic factors and caspase activation pathways during the postmortem aging of beef muscle. (1st January 2016) - Huang, Feng; Huang, Ming; Zhang, Hong; Zhang, Chunjiang; Zhang, Dequan; Zhou, Guanghong
Highlights: We examine the pathways to apoptosis in postmortem (PM) beef muscle. Cytochrome c was released from mitochondrion to cytoplasm. Mitochondrial pathway is one of the apoptosis pathway in postmortem beef muscle. Bax and Hsp27 were two key apoptotic factors in the apoptosis of PM beef muscle. Abstract: The pathway of apoptosis (effector caspase activation) in beef muscle cells was investigated by examining the expression of apoptotic factors during postmortem (PM) storage of beef muscle. Results showed that caspase-3 could be activated in PM beef muscle. The expression of cytochrome c increased in the cytosolic fraction but significantly decreased in the mitochondrial fraction in the early PM period, which demonstrated that cytochrome c was released from mitochondrion to cytoplasm. The expression of the anti-apoptotic factor Bcl-2 did not show any visible change, and that of pro-apoptotic factor Bax increased during PM storage. Expression of the heat-shock protein Hsp27 significantly decreased with increased PM time. These results demonstrated that the mitochondrial pathway was one of the apoptosis pathways in PM beef muscle and that Bax and Hsp27 were two key regulation factors in apoptosis in PM beef muscle.